Effect of life skills education on socio-emotional functioning of adolescents in urban Puducherry, India: A mixed-methods study - Gayathri Surendran; Sonali Sarkar; Preeti Kandasamy; Tanveer Rehman; Salin Eliyas; Manikandanesan Sakthivel (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: We wanted to assess the effect of life skills education (LSE) and regular curriculum on the self-esteem, self-efficacy, adjustment, and psychosocial functioning of students from co-educational government schools, compared to those receiving only the regular curriculum. The secondary objectives were to study the feasibility of such sessions and identify the factors affecting the effectiveness of the sessions. MATERIALS AND METHODS: We conducted a mixed-methods study in government schools of urban Puducherry, India in 2018-2019. The quantitative component was a cluster-randomized trial with activity-based learning methods delivered over 10 sessions in the intervention arm (IA). Differences in outcome variables (self-esteem, self-efficacy, adjustment, psychosocial behavior) between baseline and after intervention in each of the groups were calculated, and the difference-in-differences (DID) technique was applied to account for any natural change in scores over time. Qualitative data were collected through focused group discussions (FGDs) among students and teachers. Analysis was founded on a positivist paradigm with inducto-deductive methodology. RESULTS: The mean (SD) age of 258 participants was 13 (1) years in both arms. The mean (SD) difference between baseline and end-line for IA and control arm (CA) was 0.3 (4.4) and − 0.1 (4.0), for self-esteem (P = 0.38), 0.03 (6.0) and − 1.1 (6.1) for self-efficacy (P = 0.12), and − 0.04 (3.5) and − 0.05 (4.3) for adjustment (P = 0.73), respectively. Similarly, the median (interquartile range [IQR]) difference in the conduct problems scale of the Strengths and Difficulties Questionnaire was − 1 (−2, 1) and 0 (−1, 1) (P < 0.01). Five FGDs revealed multiple positive effects on anger management, conduct, self-awareness, and responsible behavior. All 10 teachers viewed life skills education (LSE) positively. CONCLUSIONS: LSE positively affects adolescents' socio-emotional functioning, but more extended periods of exposure are needed to demonstrate discernible change. The feasibility of implementation depends on the syllabus and based on health policies.